Profound Iron Deficiency Anemia and Irreversible Dilated Cardiomyopathy in a Child - Samuel G. Wittekind; Hugo R. Martinez; Chet Villa; Matthew Bacon; Adrienne M. Hammill; Angela Lorts (Case Reports in Cardiology)
Iron deficiency anemia has been associated with a secondary and potentially reversible cardiomyopathy. The pathophysiologic paradigm has been that the hematologic disease begets cardiac dysfunction. There may be, however, a point at which myocardial injury is irreversible in susceptible individuals. We present the case of a 4-year-old, developmentally normal, child who presented with iron deficiency anemia and a dilated cardiomyopathy with congestive heart failure. Despite appropriate correction of the anemia, the patient developed decompensated heart failure requiring milrinone therapy and eventual heart transplantation. This report will alert clinicians to the potential for irreversible adverse cardiac remodeling and the importance of close pediatric cardiology consultation and serial assessment in order to implement appropriate heart failure therapy.